Could We Derive Benefit From Implementing Electronic Medical Records In Hospital?: A Structured Evidence and Narrative Review - Rahmawati, Sarah Rosiana (UHAMKA Press, 2018)
Introduction One method chosen by many hospitals to achieve efficiency is the use of an Electronic Medical Record (EMR) system. This study discusses the EMR and its relationship with the efficiency and quality of hospital services through patient outcomes and users? (physicians? and nurses?) perspectives. Method A structured evidence and narrative review using the PRISMA method, with articles retrieved from online databases including PubMed, Wiley, ScienceDirect and ProQuest. The study?s period of review dates back ten years. Results The advantages of EMRs are decreased length of stay (LOS) and infection rate, plus a reduced probability of readmission once a patient safety event has occurred. EMRs reduce nurse, licensed vocational nurse (LVN) and registry cost per hour. EMRs provide enhanced ability in completing medical records and clinical documentation. The disadvantages are greater inefficiency in medical-surgical acute settings and increased cost per patient day. EMR does not reduce LOS in ICU. Some physicians also complain about the inefficiencies and time loss created by EMR. Conclusion The implementation of EMR in hospitals has advantages and disadvantages. Hospital management should undertake more analysis and consideration prior to deciding whether or not to use EMR. Keywords: Electronic medical records, hospital, patients? outcomes, efficiency